2022
DOI: 10.1186/s12935-021-02425-6
|View full text |Cite
|
Sign up to set email alerts
|

PHD finger protein 20-like protein 1 (PHF20L1) in ovarian cancer: from its overexpression in tissue to its upregulation by the ascites microenvironment

Abstract: Background Ovarian cancer is the most aggressive gynecological malignancy. Transcriptional regulators impact the tumor phenotype and, consequently, clinical progression and response to therapy. PHD finger protein 20-like protein 1 (PHF20L1) is a transcriptional regulator with several isoforms, and studies on its role in ovarian cancer are limited. We previously reported that PHF20L1 is expressed as a fucosylated protein in SKOV-3 cells stimulated with ascites from patients with ovarian cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…For example, TGF‐β, a growth factor present in most AFs, is directly or indirectly associated with promoting the proliferation of ovarian cancer cells (Puiffe et al, 2007), and in emphysema‐like phenotype in core fucosa‐deficient mice (Wang et al, 2005). On the other hand, the increase in total fucosylation was a generalized effect of the five AFs on the three cell lines, as has been previously reported by our group on cell surface fucosylation and tissues derived from tumors (Alberto‐Aguilar et al, 2022; Villegas‐Pineda et al, 2015), a process that has been poorly studied in ovarian cancer. Epidermal Growth Factor (EGF) is also a reported factor in AF (Maihle et al, 2002), and has been shown to participate in the progression of ovarian cancer.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, TGF‐β, a growth factor present in most AFs, is directly or indirectly associated with promoting the proliferation of ovarian cancer cells (Puiffe et al, 2007), and in emphysema‐like phenotype in core fucosa‐deficient mice (Wang et al, 2005). On the other hand, the increase in total fucosylation was a generalized effect of the five AFs on the three cell lines, as has been previously reported by our group on cell surface fucosylation and tissues derived from tumors (Alberto‐Aguilar et al, 2022; Villegas‐Pineda et al, 2015), a process that has been poorly studied in ovarian cancer. Epidermal Growth Factor (EGF) is also a reported factor in AF (Maihle et al, 2002), and has been shown to participate in the progression of ovarian cancer.…”
Section: Discussionsupporting
confidence: 80%
“…It has been reported that fucosylation could vary between cell types and tissues (Alberto‐Aguilar et al, 2022). The presence of highly fucosylated antigens expressed on the surface of transformed cells is attributed to increased expression of FUTs and correlates with poor prognosis in colorectal cancer (Nakagoe et al, 2000; Puiffe et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PHF20L1 influences the tumor landscape by altering transcriptional dynamics, significantly impacting clinical outcomes and therapy responsiveness in ovarian cancer. The study underscores PHF20L1's potential as a therapeutic target, given its correlation with diminished patient survival rates (Alberto-Aguilar et al, 2022).…”
Section: Chromatin Structure Regulation In Cancer Progressionmentioning
confidence: 80%
“… 21 A previous study found that the expression of PHF20L1 was increased in tumor tissue sections of patients with ovarian cancer. 22 Based on the ceRNA regulatory network in Figure 5A , circPHF20L1/miR-29a-3p/Col6a2 may play a regulatory role in the development of myocardial fibrosis in DCM. The overexpression of circCLASP1, the third upregulated circRNA in the present study, greatly enhanced the stimulating effects of Huaier-induced immunogenic cell death.…”
Section: Discussionmentioning
confidence: 99%